Mediators of socioeconomic differences in overweight and obesity among youth in Ireland and the UK (2011-2021): a systematic review - Frances M. Cronin; Sinead M. Hurley; Thomas Buckley; Delfina Mancebo Guinea Arquez; Naeha Lakshmanan; Alice O'Gorman; Richard Layte; Debbi Stanistreet (BMC, 2022)
Abstract Background By 2025, adult obesity prevalence is projected to increase in 44 of 53 of European-region countries. Childhood obesity tracks directly onto adult obesity, and children of low socioeconomic position families are at disproportionately higher risk of being obese compared with their more affluent peers. A previous review of research from developed countries identified factors mediating this relationship. This systematic review updates and extends those findings specifically within the context of Ireland and the United Kingdom. Objective The aim of this systematic review is to summarise peer-reviewed research completed in Ireland and the United Kingdom between 2011-2021 examining mediators of socioeconomic differentials in adiposity outcomes for youth. Design An electronic search of four databases, Ovid MEDLINE, Embase, Web of Science and EBSCOhost was conducted. Quantitative studies, published in the English language, examining mediators of socioeconomic differentials in adiposity outcomes in youth, and conducted in Ireland and the United Kingdom between 2011-2021 were included. An appraisal of study quality was completed. The systematic review followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Results Following screening, a total of 23 papers were eligible for inclusion. Results indicate socioeconomic differentials for Ireland and the United Kingdom follow similar patterns to other developed countries and have similar mediating factors including early life and parent-level factors. However, this review identified additional factors that mediate the relationship, namely access to green space and favorable neighborhood conditions. Identifying these factors present further opportunities for potential interventions and confirm the requirement for tailored and appropriate research and interventions for Ireland and the United Kingdom. Conclusion This review identified several modifiable factors that should be considered when planning interventions aimed at reducing socioeconomic differentials in adiposity among youth in Ireland and the United Kingdom. Support was found for interventions to be made as early as possible in an at-risk child's life, with the prenatal and preschool periods considered the most efficacious. Results were equivocal about the role of physical activity in the risk of childhood overweight and obesity. While multi-country analyses provide excellent overviews, country- or area-specific research may produce more nuanced, and potentially more powerful findings, which can help better inform policy responses and interventions.